Evaluating the role of Cardiac Genetics Nurses in inherited cardiac conditions services using a Maturity Matrix. (1st October 2014) - Kirk, Maggie; Simpson, Amy; Llewellyn, Mark; Tonkin, Emma; Cohen, David; Longley, Marcus
Abstract: Background: Cardiovascular disease is a leading cause of death worldwide and genetic risk factors play a role in nearly all such cases. In the UK, health service capacity to meet either current or future estimated needs of people affected by inherited cardiac conditions (ICCs) is inadequate. In 2008 the British Heart Foundation funded nine three-year Cardiac Genetics Nurse (CGN) posts across England and Wales to enhance ICC services. The CGNs were experienced cardiac nurses who had additional training in genetics and acted to coordinate cardiac and genetics service activities. Aim: To create and apply a framework against which progress in ICC service improvement could be measured over time following the CGN appointments. Methods: A performance grid (Maturity Matrix, MM) articulating standards in five domains against stages of ICC service development was created by stakeholders through a consensus approach. The MM was used to guide staged self-assessments by the CGNs between 2009 and 2011. A six-point scale was used to locate progress from 'emerging' to 'established', represented graphically by spider diagrams. Results: Progress in all domains was significant for new, emerging and established services. It was most notable for effective utilisation of care pathways and efficient running of clinics. Commitment to family-centred care was evident. Conclusion: The ICC-MM provided a comprehensive framework for assessing ICC services and has merit in providing guidance on development. CGNs can help integrate care across specialisms, facilitating the development of effective and sustainable ICC services at new, developing, and more established ICC service locations.